IMPACT OF PERCEIVED USEFULNESS, PERCEIVED EASE OF USE AND CONSUMER TRUST ON BEHAVIORAL INTENTION - Reta Tata Pratiwi; Purwanto SK; Nina Nurhasanah (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
This study aims to examine and analyze the effect of Perceived Usefulness, Perceived Ease of Use and Consumer Trust both partially and simultaneously on Behavioral Intention in the Traveloka Application. The research approach used in this research is quantitative research. The population in this study are consumers who use the Traveloka application. Data was collected using the survey method by distributing questionnaires to respondents who have purchased tickets through the Traveloka application, purchased tickets using the Traveloka application in the last 6 months and are in the Jabodetabek area. Questionnaires collected as many as 150 respondents, the data is then processed using multiple linear regression methods. Results of data analysis performed with the help of SPSS tools. Based on the results of this analysis it is known that the variables Perceived Usefulness, Perceived Ease of Use and Consumer Trust simultaneously have a positive effect on Behavioral Intention in the Traveloka Application. Partially the variables Perceived Usefulness, Perceived Ease of Use and Consumer Trust have proven to have a positive effect on Behavioral intention in the Traveloka Application. It can be stated that the easier the use of the Traveloka Application, the better the benefits of the application, and the greater the consumer trust, which leads to an increased intention to use the Traveloka Application. It is expected that the findings of this research, along with support from other studies, can provide a strong foundation for guiding the future development of the Traveloka application.